Room-temperature macromolecular serial crystallography using synchrotron radiation. (2014) - Stellato, F.; Oberthür, D.; Liang, M.; Bean, R.; Gati, C.; Yefanov, O.; Barty, A.; Burkhardt, A.; Fischer, P.; Galli, L.; Kirian, R. A.; Meyer, J.; et al.
No abstract available